2020
DOI: 10.3390/molecules26010030
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Analogue L48H37 Suppresses Human Osteosarcoma U2OS and MG-63 Cells’ Migration and Invasion in Culture by Inhibition of uPA via the JAK/STAT Signaling Pathway

Abstract: Osteosarcoma, the most prevalent malignant bone tumor in the pediatric age group, is responsible for the great majority of cancer-associated deaths owing to its highly metastatic potential. The anti-metastatic effects of the new curcumin analogue L48H37 in human osteosarcoma are still unknown; hence, we investigated whether L48H37 represses human osteosarcoma cells’ biological behavior of migratory potential and invasive activities and attempted to delve into its underlying mechanisms. L48H37 up to 5 μM inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
(22 reference statements)
0
25
0
Order By: Relevance
“…For example, diphenyl difluoroketone (EF-24), with higher oral bioavailability (60%) than curcumin, was reported to trigger cell apoptosis in human acute myeloid leukemia cells [ 20 , 21 ]. In addition, L48H37, with a more stable structure than curcumin, can inhibit the migration and invasion ability of human osteosarcoma [ 22 ]. FLLL32 has better cytotoxicity than curcumin in colorectal cancer, glioblastoma, multiple myeloma, and liver cancer [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, diphenyl difluoroketone (EF-24), with higher oral bioavailability (60%) than curcumin, was reported to trigger cell apoptosis in human acute myeloid leukemia cells [ 20 , 21 ]. In addition, L48H37, with a more stable structure than curcumin, can inhibit the migration and invasion ability of human osteosarcoma [ 22 ]. FLLL32 has better cytotoxicity than curcumin in colorectal cancer, glioblastoma, multiple myeloma, and liver cancer [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway is an important signal pathway that regulates message transmission from outside the cell membrane to the nucleus, and it is closely related to cell proliferation, survival, differentiation, apoptosis, and other physiological processes [ 36 ]. Previous studies have pointed out that curcumin and its analogs promoted the apoptosis of cancer cells through the MAPK pathway and downstream caspase activation in several types of cancer [ 22 , 37 , 38 ]. In oral cancer, tetrahydrocurcumin (THC), a metabolite of curcumin, promoted G2/M arrest and apoptosis via the activation of the p38 pathway [ 39 ], and the curcumin analog DMC could also induce G2/M arrest and apoptosis through the p38 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…JAK1 and JAK3 activate STATs by phosphorylation (21). It has been previously reported that JAK/STAT signaling is involved in several important cellular processes, including cell proliferation, migration, apoptosis and inflammation (41)(42)(43). A number of studies have suggested that JAK/STAT signaling is involved in the pathogenesis of tissue and organ I/R injury, including intestinal I/R injury (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…FLLL32 however showed very little inhibition of RTKs like EGFR, HER2 and Met ( Lin et al, 2010b ). Another curcumin analogue, L48H37, also decreased the phosphorylation of JAK1, JAK2, JAK3, and STAT3 in osteosarcoma cells ( Lu et al, 2020 ). Gene expression profiling and recent RNA sequencing technology also identified both upregulation and downregulation of JAK/STAT signaling pathway components, with some of these studies also documenting changes in RTK gene expression ( Van Erk et al, 2004 ; Teiten et al, 2009 ; Zhao W. et al, 2015 ).…”
Section: Receptor Tyrosine Kinase Signaling Pathways Targeted By Curcumin In Cancermentioning
confidence: 99%